The Importance of Job Analysis, Experience, Satisfaction, and Organizational Commitment - Mirozha, Eidho; Awan, Soni Harsono; Prawitowati , Tjahjani (International Research Journal of Business Studies, 2025)
This study aims to examine the influence of job analysis and work experience on employee performance, with job satisfaction as a mediating variable and organizational commitment as a moderating variable. A quantitative approach was used with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method, involving 170 employees from four Community Health Centers (Puskesmas) in Semampir District, Surabaya. Data were collected through a validated questionnaire and analyzed using SmartPLS 3.0. The results showed that job analysis and work experience did not directly affect performance, but significantly influenced job satisfaction. Job satisfaction significantly influenced performance and fully mediated the influence of job analysis and work experience on performance. In addition, organizational commitment significantly moderated the relationship between job satisfaction and performance. These findings confirm the central role of job satisfaction and the importance of organizational commitment in improving employee performance in primary healthcare.